GREEN HRM SEBAGAI STRATEGI KEPALA SEKOLAH UNTUK MEMBANGUN BUDAYA SEKOLAH BERKELANJUTAN PADA SD NEGERI MANTIMIN 2 KABUPATEN BALANGAN - Muhammad Raili; Khuzaini; Syahrial Shaddiq (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This research aims to analyze the Green Human Resource Management (G-HRM) strategy implemented by the Principal of SD Negeri Mantimin 2, Balangan Regency, and its contribution to building a sustainable school culture. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, teachers, and educational staff, supported by observation and documentation. Thematic analysis was used for data analysis. The findings reveal that the principal implemented a systematic G-HRM strategy covering three pillars: green recruitment, green training (practical skills), and green performance management. A key finding was the integration of pro-environmental aspects into the teacher performance appraisal (SKP), which served as the main driver for behavior change. This G-HRM strategy significantly contributed to forming a sustainable culture. The process transformed from forced compliance (due to evaluation) into habituation, and eventually internalized into social norms (culture). G-HRM proved to be an effective managerial mechanism for translating a sustainability vision into tangible practices in an elementary school setting.